2013
DOI: 10.1002/jctb.4161
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the tire derived rubber (TDR) medium for wastewater treatment under aerobic and anaerobic conditions

Abstract: BACKGROUND:The present study evaluated the effectiveness and durability of TDR for biofilm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…When TDR was incubated (30 ± 2 °C) with activated sludge showed comparatively higher biofilm development (0.51 g) and physiological activities under aerobic conditions even after 7 weeks. 33 Khan et al 34 found that the starting phase of the stone media FBR was reduced after incubation of the stones with activated sludge for two weeks. In another research study, it was observed that the starting phase of the TF systems packed with different filter media was reduced (36 h at low and 24 h at mesophilic temperature regimes) after inoculation with activated sludge for 14 days for achieving effective treatment of wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…When TDR was incubated (30 ± 2 °C) with activated sludge showed comparatively higher biofilm development (0.51 g) and physiological activities under aerobic conditions even after 7 weeks. 33 Khan et al 34 found that the starting phase of the stone media FBR was reduced after incubation of the stones with activated sludge for two weeks. In another research study, it was observed that the starting phase of the TF systems packed with different filter media was reduced (36 h at low and 24 h at mesophilic temperature regimes) after inoculation with activated sludge for 14 days for achieving effective treatment of wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…The influent trickling over the filter media produces biofilm that covers the filter media. This biofilm consists primarily of bacteria, protozoa, algae, and fungi (about 0.1 to 0.2 mm thick) [13][14]33]. As the wastewater flows over the biofilm, organic matters are degraded into carbon dioxide and water due to the metabolic activity of the microbes.…”
Section: Trickling Filter System Design Operation and Applicationmentioning
confidence: 99%
“…Bacterial count (Escheria coli and feacal coliforms), COD, BOD, pH, NO -2 , NO -3 , PO 4 -3 , SO 3 -2 [33] Integrated Wastewater Treatment System (i.e., Aeration, Coagulation and Advance Oxidation Processes) Carwash industry wastewater COD, TDS, turbidity, DO, pH, and oil contents [34] Constructed economic limitations and consequences of the decision [16]. Unnecessarily costly treatment will divert scarce resources away from other development projects [17].…”
mentioning
confidence: 99%
“…Effective media plays a key role in the development of microbial community/biofilm. Several biofilm support media have been used to increase the performance of a trickling filter, such as rocks/plastic [14], a nylon pot scrubber [18], commercial rings (e.g., crushed leca, kaldnes, and Norton), calcitic gravel [15][16], luffa cylindrical [19], geotextile [20], pall rings [21], polyurethane foam pores [22], coal cinder [23], tire-derived drubber [24], oyster shell [25], corrugated plastic sheet [26], stone [27], gravel and zeolite [28], sponge [29], zeolite and ceramsite [30], polypropylene plastic [31], biochar chips [32], and ceramic particles [33]. These are either costly or not easily available by small landholder farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these materials (e.g., plastic, geotextiles, commercial rings, polyurethane foam, tire-derived rubber, sponge, biochar chips, and ceramics) are being prepared synthetically and cannot work without introducing specific seeding/ acclimatization of the microbial community. It would eventually increase operational costs of the treatment system [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Moreover, technically trained human power is required to operate the treatment systems and also not easily available by the small landholder farmers.…”
Section: Introductionmentioning
confidence: 99%